Women in the world today - United States Department of State Bureau of International Information Programs; BC Open Textbook Project; BCcampus (Department of State Bureau of International Information Programs, 2012)
"Global Women's Issues and the Beijing Platform for Action. This book is based on the 12 critical areas of concern identified at the Beijing Conference: 1 The persistent and increasing burden of poverty on women 2 Inequalities and inadequacies in and unequal access to education and training 3 Inequalities and inadequacies in and unequal access to health care and related services 4 Violence against women 5 The effects of armed or other kinds of conflict on women, including those living under foreign occupation 6 Inequality in economic structures and policies, in all forms of productive activities and in access to resources 7 Inequality between men and women in the sharing of power and decision- making at all levels 8 Insufficient mechanisms at all levels to promote the advancement of women 9 Lack of respect for and inadequate promotion and protection of the human rights of women 10 Stereotyping of women and inequality in women's access to and participation in all communication systems, especially in the media 11 Gender inequalities in the management of natural resources and in the safeguarding of the environment 12 Persistent discrimination against and violation of the rights of the girl child."--BCcampus website.
This work is licensed under the Creative Commons Attribution-NonCommercial-ShareAlike License.
This bibliographic record is available under the Creative Commons CC0 "No Rights Reserved" license.
Description based on version viewed on BCcampus OpenEd website; title from pdf title page.
Keywords: Women -- Social conditions -- Textbooks; Electronic books